Dimethyl Fumarate Induces Metabolic Crisie to Suppress Pancreatic Carcinoma - Chen, Kaiyuan; Wu, Shanshan; Ye, Sisi; Huang, Huimin; Zhou, Yi; Zhou, Hongfei; Wu, Shijia; Mao, Yefan; Shangguan, Fugen; Lan, Linhua; Chen, Bicheng (Frontiers in Pharmacology, 2021)
Dimethyl fumarate (DMF) is an approved drug used in the treatment of multiple sclerosis (MS) and psoriasis therapy. Multiple studies have demonstrated other pharmacological activities of DMF such as an anticancer agent. In particular, studies have shown that DMF can modulate the NRF2/HO1/NQO1 antioxidant signal pathway and inactivate NF-κB to suppress the growth of colon and breast cancer cells, and induce cell death. In this study, we aimed to evaluate the anti-tumor activities of DMF in pancreatic cancer (PC) focusing on cell death as the predominant mechanism of response. We showed that both mitochondrial respiration and aerobic glycolysis were severely depressed following treatment with DMF and the effects could be abrogated by treatment with L-cysteine and N-acetyl-L-cysteine (NAC). Importantly, we verified that DMF induced metabolic crisis and that cell death was not related to alterations in ROS. Our data implied that MTHFD1 could be a potential downstream target of DMF identified by molecular docking analysis. Finally, we confirmed that MTHFD1 is up-regulated in PC and overexpression of MTHFD1 was negatively related to outcomes of PC patients. Our data indicate that DMF induces metabolic crisie to suppress cell growth and could be a potential novel therapy in the treatment of PC.